Age-Related Differences in Stepping Response When Stepping onto a Known Soft Surface under Dual Task Conditions. (26th May 2010) - Harada, Nobuko; Okada, Shuichi; Negoro, Shinya
Abstract : The purpose of this study was to investigate whether age-related differences in stepping response influence postural control when stepping onto a known soft surface under dual task conditions. Nine young and eleven older female adults participated. First, they stepped on a flat surface while grasping an empty cup (single task), and then they repeated the task while grasping a cup filled with water (dual task). For the second experiment, they stepped on a soft surface placed in front of them while performing the above tasks. The main result was that %DIP (initiation phase as a percentage of the total stepping task time) was significantly higher for older than for young adults during the dual task on the soft surface. In conclusion, caution due to previous experience may increase attentional demand during dual tasks and lengthen the time required for central nervous processing in order to avoid losing postural stability in older adults, resulting in reductions in step velocity and step length compared to those in young adults.